CORRELATION BETWEEN BLOOD LEAD EXPOSURE, BLOOD PRESSURE, AND HEMOGLOBIN LEVELS AMONG ONLINE MOTORCYCLE TAXI WORKERS - Prihatiningsih, Diah; Agus Ferry Sutrisna Putra, I Gusti Putu (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2023)
Lead or Pb is a byproduct of fuel combustion in vehicle engines used as an anti-knock additive. Lead exposure can worsen the quality of air contaminated by motor vehicle emissions, which can affect the performance of online motorcycle taxi drivers. This study aims to assess the relationship between blood lead levels, blood pressure, and hemoglobin levels in online motorcycle taxi drivers in Dauh Puri Kelod Village. This study is an observational study using a cross-sectional design. The sample consisted of 30 respondents selected based on their length of work, age, and daily cigarette consumption. Data were collected through questionnaires, direct measurements, and lead examinations using the AAS method. The data were analyzed using Spearman rank correlation and multiple linear regression. The results showed a significant relationship between age and blood lead levels (p=0.000 and r=0.989); there was a significant relationship between length of work and blood lead levels (p=0.000 and r=0.683); there was a relationship between the amount of cigarettes consumed and blood lead levels, although the relationship was not very strong with a correlation of (p=0.038 and r=0.381); there was no significant relationship between blood lead levels and hemoglobin levels in online motorcycle taxi drivers (p=0.369 and r=-0.170); there was a significant relationship between blood lead levels and systolic blood pressure (p=0.000 and r=0.975) and diastolic blood pressure (p=0.000 and r=0.810). It is recommended to use personal protective equipment (masks) when working in gas stations and to regularly monitor health at least once a year.